Desenvolvimento e avaliação de recurso educacional digital sobre sarcopenia na pessoa idosa para profissionais de saúde - Silva, Rávida da Rocha Lima (2023)
Population aging causes impacts on different sectors of society, being associated with a decrease in functional capabilities. When adverse muscular changes occur that accumulate throughout life, they lead to a muscular decline called sarcopenia, a disease that results in worse quality of life, physical disability, morbidities, frailty and mortality. Thus, actions aimed at preventing or detecting it early have attracted the attention of researchers and health professionals. The objective of this study was to develop and evaluate a digital educational manual for health professionals on sarcopenia in the elderly. This is a quantitative research conducted based on the Instructional Design model, in which the following phases were used: analysis, development, and evaluation. In the analysis phase, a scope review was carried out guided by the methodological recommendations proposed by the Joana Briggs Institute guidelines, following the steps of Preferred Reporting Items for Systematic Reviews and Extension of Meta-Analyses for Scope Reviews. In the development phase, a professional designer was involved, who created the illustrations using the FireAlpaca program, layout and layout, using Affinity Publisher with the support of a Gaomon® m10K 2018 graphics tablet to arrange and organize the texts and images. For evaluation, 15 health professionals were selected (nurses, doctors, physiotherapists, physical education professionals and nutritionists) who analyzed the following aspects: objectives, organization, language, writing style, appearance and relevance of the material. In data analysis, the proportion of reviewers who agreed on the positive evaluation of the items was measured, considering the percentage greater than or equal to 80%. The research project was approved by the Research Ethics Committee of the Federal University of Ceará, with opinion no. 5,777,556. The manual entitled “Guidance manual on sarcopenia in the elderly” was made in A4 size, with dimensions of 21 x 29.7 cm and a total of 30 pages. It is organized into two parts, namely: Part 1 - General aspects of sarcopenia in the elderly; Part 2 - Clinical management of sarcopenia in the elderly. Regarding the profile of the reviewers, the majority were female (60%), aged between 26 and 59 years, had a degree in nursing (46.7%), with an average time of training of 13.53 years, doctorate degree (60%), working professionally in the teaching field (60%) and with publications on the subject of geriatrics/gerontology/sarcopenia and development of digital educational resources (73.3%). The average time of experience was 12.46 years in geriatrics/gerontology, 8 years in sarcopenia, 5.13 years in development of digital educational resources and 4.46 years in evaluation. All items evaluated had an agreement rate greater than 80%, the global average was 93.6%. The manual stands out for being a unique product for professionals and included technical reviewers from different areas of healthcare. It is noteworthy that this material will be translated into Spanish in international collaboration with the Red de Enfermería de Salud del Adulto Mayor, Ecuador headquarters, and with researchers from the School of Nursing at the University of Guayaquil, increasing its range of use.